Applying “attribution theory” to determine the factors that lead to the failure of entrepreneurial ventures in Colombia (2017)
Purpose – The purpose of this paper is to use attribution theory to identify the factors that contribute to the failure of entrepreneurial ventures in Colombia. Design/methodology/approach – The research study upon which this paper is based involved an online survey. A total of 324 Colombian entrepreneurs who had experienced business failure answered this survey. The study included six factors (financial, organizational, marketing, external environment, operational, and human resources) with their respective attributions as well as a personality test and segmentation questions. Two multivariate techniques were used (principal component analysis and a multinomial distribution model) to analyze the results of the survey. Findings – The results showed that the principal attributions of failure for Colombian entrepreneurs were financial and organizational issues, the external environment, and marketing. Specific sub-issues included insufficient income generated to maintain the business, lack of proper financing, problems with the control of the business, as well as legal and economic instability. Practical implications – These results of this research study are important for the creation and development of policies that promote entrepreneurship in Colombia and other developing countries. The findings may also provide entrepreneurs with an analysis of the attributions that are most frequently associated with failure and related lessons, which could individually and cumulatively increase the probability of success for entrepreneurs who are starting new business ventures. Originality/value – This study makes an important contribution to the extant entrepreneurship literature by identifying and categorizing factors associated with business failure in Colombia. In developing countries, it is especially important to analyze failure attributions to determine relevant official policy instruments that could promote successful business ventures.